Healthcare access, attitudes and behaviours among Navajo adults during the COVID-19 pandemic: a cross-sectional study - Robin B Harris; Carmenlita Chief; Heidi E Brown; Rachelle L Begay; Priscilla R Sanderson; Breanna Lameman (BMJ Public Health)
Objective To assess factors associated with positive COVID-19 tests, perspectives on health-related care delivery during pandemic and factors supporting resilience among members of the Navajo Nation.Methods and analysis From May through October 2021, a multi-institutional team recruited participants (n=154) to complete a 49-item questionnaire or participate in a focus group (n=14) about their experience with COVID-19 and the effects on their use and access to allopathic and traditional healthcare. A multi-investigator, phenomenological approach summarised focus group experiences.Results While 73% had been tested for COVID-19, only 27.8% reported a positive test. Positive tests were not associated with household size or multigenerational homes, though time to grocery store was (p=0.04). There were no significant differences in allopathic or traditional medical care experiences from before and during the pandemic. Despite limited internet access, 28.8% chose a telehealth appointment and 42% expressed satisfaction with their experience. Discussion themes revealed perceived disruptions of healthcare needs with acknowledgement that healthcare providers were supportive throughout the Navajo Nation quarantine.Conclusion Presence of comorbidities and living in multigenerational homes do not explain the disproportionate effects of COVID-19 among American Indian communities. Strengthening family and community bonds supported resilience in these communities.